Data Retrieval from Data Warehouse Using Materialized Query Database - Chakraborty, Sonali; Doshi, Jyotika (International Journal of Computer Sciences and Engineering, 2025)
Decision making in an organization requires aggregate as well as non- aggregate results, computed from data stored in data warehouse. Performance in case of result extraction from a data warehouse is an important factor. Probability that the same query is fired more often is high. This results into frequent analysis of warehouse data for fetching same results or results with incremental updates. This paper discusses an approach for storing such frequent queries along with their result, timestamp, frequency and threshold in a separate database. Past results are fetched from database and only incremental updates are done through data marts. This approach may improve performance removing or reducing execution time.